Laser Technologies in Metal-Based Materials - Manshina, Alina A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Laser Technologies in Metal-Based Materials" offers a harmonious presentation of the recent achievements in the field of laser-induced physical and chemical phenomena that have evolved into laser techniques to produce diverse functional metal materials and structures. The presented results provide new ideas for researchers, and new solutions for science-consuming manufacturing and industry.